Assessment of Prescription Pattern of Antidiabetic Drugs in the Outpatient Department of a Tertiary Care Hospital - Ashutosh Kakade; Ipseeta Ray Mohanty; Sandeep Rai (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2017)
Background: Glycemic control remains the major therapeutic objective for prevention of arget organ damage and other complications arising from diabetes. Poor glycemic control in diabetes mellitus can be prevented by using rational use of oral hypoglycemic agents (OHA). Rational use of the drugs in populations can be effectively evaluated using drug utilization studies.  Method: Necessary approval from the Institutional Ethics Committee was obtained before initiating the study. The study was conducted in the Department of Pharmacology and Department of Medicine, MGM Medical College, Kamothe, Navi Mumbai. Two hundred twenty patients of Type II diabetes mellitus who conformed to the specifi ed Inclusion and Exclusion Criteria were enrolled for the study after taking consent. A Case record form was administered to these patients, which included details regarding the prescription pattern, socio-demographic profi le of the Type II diabetic patients. Results: Average number of drugs per prescription was found to be 2.03. None of the drugs were prescribed by generic name. Majority (70%) of the patients were on combination therapy and 30% of patients were on antidiabetic monotherapy. Biguanides accounted for (41%) of all the prescribed drugs followed by sulfonylureas (20%), DPP4 inhibitors (19%) and OHA combination therapy. Biguanides (Metformin) was the most commonly prescribed drug (84%), followed by sulfonylureas (Glimepiride) (41%) and DPP4 inhibitors [Teneligliptin (20%), Vildagliptin (18%)]. Conclusion: Metformin was the most frequently prescribed drug in diabetes. Prescription by Brand name is a matter of concern.